Exploring the link between dietary zinc intake and endometriosis risk: insights from a cross-sectional analysis of American women - Yingmei Huang; Yumei Wei; Feng Liang; Yingqin Huang; Jianyong Huang; Xuehui Luo; Baoli Xie (BMC, 2024)
Abstract Background Endometriosis is a complex disorder with genetic, immune, inflammatory, and multifactorial etiologies. Zinc, an essential trace element, plays a crucial role in various physiological processes. Dysregulation or deficiency of zinc can lead to aberrations in human physiology. However, the association between dietary zinc and endometriosis remains ambiguous. This study aimed to investigate the link between dietary zinc intake and endometriosis. Methods Utilizing cross-sectional data from the National Health and Nutrition Examination Survey, we analyzed information from American women aged 20-54 years between 1999 and 2006. After adjusting for relevant covariates, multivariable logistic regression analysis was employed to assess correlations. Results A total of 4315 women were included in the study. The multivariable logistic regression model revealed a positive correlation between dietary zinc intake and the risk of endometriosis, even after controlling for confounding variables. Relative to individuals with lower zinc consumption (≤ 8 mg/day), the adjusted odds ratio (OR) values for dietary zinc intake and endometriosis in the 8-14 mg/day and > 14 mg/day groups were 1.19 (95% CI: 0.92-1.54, p = 0.189) and 1.60 (95% CI: 1.12-2.27, p = 0.009), respectively. Conclusions Our findings suggest a positive correlation between dietary zinc intake and the prevalence of endometriosis. However, further investigations are necessary to better understand this association and explore the potential role of dietary zinc in endometriosis.